Continuous Hemoadsorption with a Cytokine Adsorber during Sepsis – a Review of the Literature. Issue 5 (May 2017) - Houschyar, Khosrow S.; Pyles, Malcolm N.; Rein, Susanne; Nietzschmann, Ina; Duscher, Dominik; Maan, Zeshaan N.; Weissenberg, Kristian; Philipps, Hubertus M.; Strauss, Catharina; Reichelt, Beate; Siemers, Frank
Sepsis is a well-recognized healthcare issue worldwide, ultimately resulting in significant mortality, morbidity and resource utilization during and after critical illness. In its most severe form, sepsis causes multi-organ dysfunction that produces a state of critical illness characterized by severe immune dysfunction and catabolism. Sepsis induces the activation of complement factor via 3 pathways and the release of inflammatory cytokines such as tumor necrosis factor alpha (TNF-α) and interleukin-1beta (IL-1β), resulting in a systemic inflammatory response. The inflammatory cytokines and nitric oxide release induced by sepsis decrease systemic vascular resistance, resulting in profound hypotension. The combination of hypotension and microvascular occlusion results in tissue ischemia and ultimately leads to multiple organ failure. Several clinical and experimental studies have reported that treatment using adsorption of cytokines is beneficial during endotoxemia and sepsis. This review article analyzes the efficacy of CytoSorb ® adsorber in reducing the inflammatory response during sepsis. The CytoSorb ® adsorber is known to have excellent adsorption rates for inflammatory cytokines such as IL-1β, IL-6, IL-8, IL-10, and TNF-α. Studies have demonstrated that treatment with cytokine adsorbing columns has beneficial effects on the survival rate and inflammatory responses in animal septic models. Additionally, several cases have been reported in which treatment with cytokine adsorbing columns is very effective in hemodynamic stabilization and in preventing organ failure in critically ill patients. Although further investigations and clinical trials are needed, treatment with cytokine adsorbing columns may play an important role in the treatment of sepsis in the near future.